High Estradiol Concentrations Induce Heat Shock Protein 70 Expression and Suppress Nuclear Factor Kappa B Activation in Human Endometrial Epithelial Cells. Issue 4 (1st October 2016) - Chen, Chin-Der; Chen, Shee-Uan; Chou, Chia-Hung; Chen, Mei-Jou; Wen, Wen-Fen; Wu, Szu-Yuan; Yang, Yu-Shih; Yang, Jehn-Hsiahn
Abstract: The high serum estradiol (E2 ) concentrations induced during in vitro fertilization are detrimental to endometrial receptivity and may result in lower embryo implantation rates. We have previously found that high E2 concentrations inhibit the activation of nuclear factor kappa B (NF-κB), leading to endometrial epithelial cell (EEC) apoptosis. The objective of this study is to investigate the signaling pathways through which high E2 results in NF-κB downregulation in EECs. Isolated human EECs were cultured in different concentrations of E2 (10 −10, 10 −9, 10 −8, 10 −7 M). The expression of heat shock protein 70 (Hsp70) and heat shock factor 1 (HSF-1) were upregulated under supraphysiological E2 (10 −7 M) concentration, whereas phosphorylated inhibitory kappa B-alpha (pI κB-α) and NF-κB p65 subunits were downregulated. Immunohistochemistry of C57BL/6 mouse EECs that were exposed in vivo to high serum E2 from the administration of 20 IU of equine chorionic gonadotropin also demonstrated the same increase in HSF-1 and Hsp70 expression and a decrease in NF-κB. Immunoprecipitation of the induced Hsp70 proteins was achieved with the addition of inhibitory κB kinase gamma (IKK-γ) antibodies, and elimination of this reaction occurred after addition of hsp70 siRNA. In conclusion, high E2 concentrations enhance HSF-1 and Hsp70 expression in EECs. The induced Hsp70 forms a complex with IKK-γ and inhibits pI κB-α, which consequently suppresses NF-κB activation.